The Transformation of the Meaning of Dalalah Qath'i and Zhanni in Fiqh Reasoning: A Comparative Analysis between the Classical and Modern Eras. - Anggar Putra; Saiful; Muhammad Salahuddin (Kalam Al Gazali: Education and Islamic Studies Journal, 2025)
The Qur'an and Sunnah as the basis of Islamic law include the concepts of qath'i (definite, not takwil) and zhanni (uncertain, can be takwil). Qath'i is limited, while zhanni allows ijtihad and interpretation. This research uses a philosophical-analytical approach with a descriptive-analytical analysis method, which focuses on literature in the form of verses of the Qur'an, Hadith, and the views of classical and contemporary scholars. Data were collected from various books of tafsir and ushul fiqh, then analyzed contextually and normatively to discuss the concept of Qath'i - Zhanni and produce relevant conclusions. The results of this study show that the importance of contextual understanding of the concepts of qath'i and zhanni in the interpretation of Islamic law is in accordance with the development of the times. The concept of qath'i establishes the basic principles of Islamic teachings that are fixed, while zhanni provides room for interpretation that can be adapted to evolving social and political conditions. The transformation approach from the more rigid classical period to the more flexible modern approach reflects the need to maintain the relevance of Islamic teachings to universal principles, such as human rights and social justice.